A new species of Chironius Fitzinger, 1826 (Squamata: Colubridae) from the Pantepui region, northeastern South America - Kok, Philippe J. R. (Zootaxa, 2010)
A new colubrid snake of the genus Chironius Fitzinger, 1826 is described from the Pantepui region, Guiana Shield, northern South America. The new species, C. challenger sp. nov., is identified as a member of the genus Chironius by its low number of dorsal scale rows (< 12), and it differs markedly from all known congeners by the combination of 10 dorsal scale rows at midbody, absence of apical pits and paravertebral keels in females, more than 149 ventrals, less than 105 divided subcaudals, anal scale single, loreal as high as long or only slightly longer than high, adults and juveniles brownish with lighter crossbands, adults with dark mottling on venter, and 39–41 maxillary teeth. A key to the Chironius species of the Guiana Shield is provided.